Criminogenic Analysis of Narcotics Users Based on the Results of an Integrated Assessment in the South Jakarta Municipality Area - Asyma D.A Sianipar (Journal of Social Research, 2025)
This study aims to identify and analyze the criminogenic typology of narcotics users handled by the South Jakarta City BNN based on the Examination Report (BAP) document and the assessment of the Integrated Assessment Team (TAT). Through a descriptive qualitative approach and thematic classification techniques on 40 documents, this study revealed that user involvement in narcotics abuse is strongly influenced by a combination of social, psychological, and structural factors. The main findings identify five criminogenic typologies, namely: (1) Social-Relational, (2) Trauma-Addictive, (3) Experimental-Hedonistic, (4) Structural-Economic, and (5) Recidivist-Trapped. Each typology shows a distinctive pattern of involvement and requires a different approach to rehabilitation. Most of the users analyzed were not part of the narcotics trafficking network, but rather individuals with vulnerable social backgrounds and high environmental pressures. The results of this study show the importance of criminogenic assessment in the rehabilitation process, as well as the need for more adaptive, evidence-based, and equitable policy reforms. This research also supports the implementation of restorative justice approaches and emphasizes the importance of cross-sectoral synergy in designing needs-based rehabilitation programs.